Screening of advanced breeding lines of castor against sucking pests: Screening of advanced breeding lines of castor against sucking pests - P DURAIMURUGAN; C LAVANYA; M BHASKAR REDDY; P DEMUDUNAIDU (Journal of Oilseeds Research, 2023)
Sucking pests viz., leafhopper and thripsare the major yield limiting biotic factors in castor. Growing resistant cultivars is an effective, eco-friendly and economical approach to manage these insect pests. Thirty three advanced breeding lines of castor were screened against the sucking pests along with susceptible and resistant checks during late kharif 2021.Among the 33 advanced lines screened, nine lines viz., MHC-9, JHB-1080, JHB-1098, SHB1075, JHB-1099, SLCH-286, MHC-46, MHC-26 and ICH-277 exhibited highly resistant reaction to leafhopper (hopper burn grade 0 on 0-4 scale). Eight lines viz., MHC-9, JHB-1080, ICH-901, JHB-1099, MHC-46, MHC-26, SHB-1073 and ICH-277 were found promising against thrips.